SEISMOTECTONIC STUDY OF THE SIBOLANGIT, NORTH SUMATRA REGION BASED ON DOUBLE-DIFFERENCE RELOCATION - Nesia S. Marbun; Aulia A. Aisjah; Anne M. M. Sirait; Yusran Asnawi; Hendro Nugroho; Andrean V. H. Simanjuntak (Institut Teknologi Sepuluh Nopember, 2025)
Sumatra is one of the most seismically active regions in the world due to the oblique convergence between the Indo-Australian and Eurasian plates, where strain is partitioned between the Sunda megathrust and the Great Sumatran Fault (GSF). While most seismicity in North Sumatra occurs along mapped strands of the GSF, several damaging earthquakes have occurred outside known fault zones, raising critical questions about hidden seismogenic structures. This study investigates the seismotectonic framework of the Karo region, with a focus on the 2017 Karo earthquake (Mw 5.6), using the double-difference relocation method. A dataset of local earthquakes recorded by the Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG) was analyzed to refine hypocenter locations, reduce uncertainties, and identify seismic clusters. Relocation results significantly improved spatial resolution, reducing average location errors to less than 3 km, and revealed clustered seismicity along a northwest–southeast trending structure offset from the Renun Fault. Depth cross-sections indicate brittle faulting within the upper crust (5–12 km), and the aftershock alignment suggests the presence of an unmapped subsidiary fault accommodating dextral shear. Comparisons with similar studies across Sumatra and Java confirm that off-fault seismicity is a common but often overlooked contributor to regional hazard. These findings underscore the importance of integrating relocated seismicity into national hazard models to account for hidden faults. By providing improved fault geometry and seismotectonic insights, this study enhances the understanding of earthquake sources in North Sumatra and supports future efforts in seismic hazard mitigation and disaster risk reduction in one of Indonesia’s most vulnerable regions.